2017
DOI: 10.1038/aps.2017.57
|View full text |Cite
|
Sign up to set email alerts
|

Influences of renal function descriptors on population pharmacokinetic modeling of vancomycin in Chinese adult patients

Abstract: Vancomycin, a glycopeptide antibiotic for the treatment of grampositive infections, is mainly eliminated via glomerular filtration. Thus, its therapeutic effects are affected predominantly by renal function. The aim of this study was to develop a population pharmacokinetic model of vancomycin for Chinese adult patients and to investigate the influence of different renal function descriptors on the predictability of the model. A retrospective analysis was performed based on the blood concentrations of vancomyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 47 publications
3
19
0
2
Order By: Relevance
“…An appropriate PPK model is of importance for achieving vancomycin targeted C ss . Traditionally, vancomycin dosage was determined based on the CLcr estimated by Scr, and most of the vancomycin PPK models were focused on the CLcr . However, many other studies had shown that cystatin C predicted vancomycin trough levels better than Scr in hospitalized patients, and a vancomycin dosing nomogram based on GFR estimated by cystatin C could improve goal trough achievement compared to Scr .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An appropriate PPK model is of importance for achieving vancomycin targeted C ss . Traditionally, vancomycin dosage was determined based on the CLcr estimated by Scr, and most of the vancomycin PPK models were focused on the CLcr . However, many other studies had shown that cystatin C predicted vancomycin trough levels better than Scr in hospitalized patients, and a vancomycin dosing nomogram based on GFR estimated by cystatin C could improve goal trough achievement compared to Scr .…”
Section: Discussionmentioning
confidence: 99%
“…The guideline of therapeutic drug monitoring for vancomycin recommends that vancomycin dosage should be administered and adjusted individually based on PPK models . PPK models of vancomycin were very common, but most of them incorporated the CLcr as the renal function covariate, which are considered to be defective in estimating renal function. There were only a few PPK models developed optimal dosing regimens according to different CLcr levels .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical guidelines recommend always keeping trough vancomycin concentrations above 10 μg/mL, and a trough vancomycin concentration of 15-20 μg/mL is recommended in more serious infections [3]. As the elimination of vancomycin relies almost exclusively on glomerular filtration, renal function is one of the most important factors influencing patient exposure to vancomycin [4].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, patients with hemorrhagic stroke had higher values of vancomycin clearance [ 7 ]. Renal function was identified as an important determinant of vancomycin clearance in several other studies, but only in some studies it was observed that declining creatinine clearance with old age contributed to decreased vancomycin clearance [ 8 ]. However, determinants of vancomycin clearance were not analyzed separately in populations with different levels of renal function, which could be why some important factors could have been missed.…”
Section: Introductionmentioning
confidence: 99%